Character attachment in team-based first person shooter game with respect to the role in the combat among Korean young gamers - Doo Heon Song; Seunghun Lee (Institute of Advanced Engineering and Science, 2021)
Character attachment have been studied thoroughly from the view of psychology and media researches. In game playing, the player-avatar relationship is a form of character attachment and affects a good game design as well as management systems such as character customizing and in game purchasing policy. In this paper, we investigate such player-avatar relationship on the theme of team-based FPS where in general the attachment is not expected to be high. However, from the online survey for Tom Clancy’s Rainbow 6 Siege mania groups, we find that there are different character attachment patterns with respect to the role of players in the team–attacker, defender, and supporter. It shows that attackers think avatar as an ‘object, but the defenders show more ‘avatar as others’ than the attackers. The supporters show high responsibility for the avatar and their play style is most like ‘avatar as symbiote’ manner.